Meat allergy: Investigation of potential allergenic proteins in beef - Han, G.D. (Niigata Univ. (Japan)); Matsuno, M; Ito, G; Ikeuchi, Y; Suzuki, A (Bioscience, biotechnology, and biochemistry, 2000)
The potential allergenic proteins in beef were investigated. The sera of ten beef-allergic patients suffering from atopic dermatitis and having a positive RAST score to beef, aged 3-18 years, were obtained from Yoshida Hospital in Japan, and five non-allergic individuals were subjected to this study. The sera of the ten patients reacted strongly to a beef extract, but not to pork and chicken extracts by both ELISA and immunoblotting. The sera of the five control subjects did not react to any of these meat extracts. Three bands having molecular masses of ~200 kDa, ~67 kDa and ~60 kDa were observed by immunoblotting after SDS-PAGE. Two fractions of the beef extract from a Sephadex-gel (G-200) filtration column strongly reacted with the sera of the beef-allergic patients by ELISA and immunoblotting: one fraction had the ~67 kDa component and the other had the ~200 kDa and ~60 kDa components. One of them (~67 kDa) was confirmed to be bovine serum albumin (BSA) by an analysis of the N-terminal amino acid sequence. We could not identify the others by sequencing, but the ~200 kDa and ~60 kDa components were presumed to be glycoproteins. Bovine gamma globulin (BGG: M.W. ~160 kDa) is a glycoprotein and has several subunits. The beef-allergic patients showed strong reactivity to the ~200 kDa and ~60 kDa components of pure BGG by immunoblotting. Inhibition-ELISA showed that pure BGG preparations strongly inhibited the binding of sera from the beef-allergic patients to the beef extract. These results suggest that the ~200 kDa, ~67 kDa and ~60 kDa components in the beef extract had strong allergenicity: ~67 kDa was BSA, and ~200 kDa and ~60 kDa were presumably aggregated BGG and it's heavy chain, respectively.